Risk of preterm birth in a twin pregnancy after an early‐term birth in the preceding singleton pregnancy: a retrospective cohort study. (8th January 2020) - Berveiller, P; Rousseau, A; Rousseau, M; Bitumba, I; Goffinet, F; Rozenberg, P
Abstract : Objective: To evaluate whether a history of spontaneous early‐term birth (37 +0 –38 +6 weeks of gestation) in the previous singleton pregnancy is a risk factor for preterm birth (PTB) in a subsequent twin pregnancy. Design: Retrospective cohort study. Settings: Two French university hospitals (2006–2016). Population: All women who delivered twins from 24 +0 weeks after a preceding singleton pregnancy birth at 37 +0 to 41 +6 weeks. Methods: Multivariate logistic regression analysis of association between twin PTB and a previous spontaneous singleton early‐term birth. Main outcome measures: Twin PTB rate before 37, 34 and 32 weeks of gestation. Results: Among 618 twin pregnancies, 270 were born preterm, 92 of them with a preceding spontaneous singleton early‐term birth. The univariate analysis showed a significantly higher risk of twin PTB before 37, 34 and 32 weeks among those 92 women compared with those with a full‐ or late‐term birth in their previous singleton pregnancy. This association remained significant after logistic regression (odds ratio [OR] between 2.42 and 3.88). The secondary analysis, restricted to the twin pregnancies with spontaneous PTB found similar results, with a risk of PTB before 37, 34 and 32 weeks significantly higher among women with a previous spontaneous singleton early‐term birth, including after logistic regression analysis (OR between 3.51 and 3.56). Conclusion: A preceding spontaneous singleton early‐term birth is a strong and easily identified risk factor for PTB in twin pregnancies. Tweetable abstract: Spontaneous 'early‐term' birth of a singleton is a significant risk factor for future preterm births in twin pregnancies. Tweetable abstract: Spontaneous 'early‐term' birth of a singleton is a significant risk factor for future preterm births in twin pregnancies.